Orders of Recombination in Complete Perovskite Solar Cells – Linking Time‐Resolved and Steady‐State Measurements. Issue 45 (20th October 2021) - Wolff, Christian M.; Bourelle, Sean A.; Phuong, Le Quang; Kurpiers, Jona; Feldmann, Sascha; Caprioglio, Pietro; Marquez, Jose Antonio; Wolansky, Jakob; Unold, Thomas; Stolterfoht, Martin; Shoaee, Safa; Deschler, Felix; et al.
Abstract: Ideally, the charge carrier lifetime in a solar cell is limited by the radiative free carrier recombination in the absorber which is a second‐order process. Yet, real‐life cells suffer from severe nonradiative recombination in the bulk of the absorber, at interfaces, or within other functional layers. Here, the dynamics of photogenerated charge carriers are probed directly in pin‐type mixed halide perovskite solar cells with an efficiency >20%, using time‐resolved optical absorption spectroscopy and optoelectronic techniques. The charge carrier dynamics in complete devices is fully consistent with a superposition of first‐, second‐, and third‐order recombination processes, with no admixture of recombination pathways with non‐integer order. Under solar illumination, recombination in the studied solar cells proceeds predominantly through nonradiative first‐order recombination with a lifetime of 250 ns, which competes with second‐order free charge recombination which is mostly if not entirely radiative. Results from the transient experiments are further employed to successfully explain the steady‐state solar cell properties over a wide range of illumination intensities. It is concluded that improving carrier lifetimes to >3 µs will take perovskite devices into the radiative regime, where their performance will benefit from photon‐recycling. Abstract : To enhance the photovoltaic performances of perovskite solar cells, an in‐depth understanding of recombination processes in full devices is necessary. To gain this insight, transient opto‐electronic measurements are applied, revealing that in full devices a superposition of first‐, second‐, and third‐order recombination fully describes the recombination adequately, nonradiative first‐order recombination dominating under solar illumination conditions.